Lessons from the Norwegian ATM System. - Hole, K.J (IEEE Security and privacy : building confidence in a networked world)
This case study focuses on real-world ATM card misuse, illustrating how too much secrecy led to a deterioration of PIN-based authentication procedures, and why a bank's refusal to share technical information is a threat to customers during a conflict.